Passiflora acreana, a new species of Passiflora subgenus Passiflora (Passifloraceae sensu stricto) from Acre, Brazil - Mezzonato-Pires, Ana Carolina; Silveira, Marcos; Honório De Oliveira, Mayk (Phytotaxa, 2023)
The new species described here was collected during expeditions carried out in the Lago do Amapá Environmental Protection Area, located in Acre State, Brazil. Morphological analysis and comparisons with close species confirmed that the collected specimens are a new species for science. Passiflora acreana was placed in P. subg. Passiflora, sect. Granadillastrum Triana & Planch., and can be distinguished by the presence of foliaceous, reniform, awned stipules, 4–8 pedunculate petiolar glands, with apex concave, and corona with 10 series of filaments. Descriptions, illustrations, distribution map, and conservation status are presented.